Does Lintner Model Explain Dividend Payments of the Indian Banking Sector ? - Nusrathunnisa; Duraipandian, R. (Indian Journal of Finance, 2019)
The present paper attempted to explain the applicability of Lintner models of dividend policy in the banking sector in India. This study was based upon a sample of 21 public and private banks belonging to the Indian banking sector for the period from 2006 to 2015. Lintner’s basic model, cash flow model, and segregated cash flow model were found to be the most appropriate in explaining the dividend behaviour in case of constituent banks of the Indian banking sector. Panel data models were used to validate Lintner models of dividend policy. The explanatory variables such as EPS, lagged dividend, cash flow, and capex were found to be the most important variables that affected the current dividend policy of the Indian banks. On the practical dimension, such information should help the banking firms in creating appropriate strategies to improve the dividend payment and firms’ performance.